Systemic treatment of colorectal cancer. - Tebbutt, N; Cattell, E; Midgley, R; Cunningham, D; Kerr, D (2002)
Palliative and adjuvant treatment for colorectal cancer has been, until recently, largely dependent on 5-fluorouracil (5-FU)-based chemotherapy. Oral fluoropyrimidines have been evaluated in the advanced disease setting and they appear to be as effective as 5-FU, but are safer and more convenient for most patients. Irinotecan and oxaliplatin are new cytotoxic agents, which are active in 5-FU-resistant disease, but which may also be combined with 5-FU as initial therapy in advanced disease. Initial combination therapy leads to improved response rates and more prolonged progression-free survival compared with 5-FU monotherapy. Standard regimens for adjuvant therapy usually involve 6 months of chemotherapy using 5-FU and folinic acid. Recent trials of capecitabine, oxaliplatin and irinotecan in the adjuvant setting are ongoing, or have recently completed accrual, and may lead to a change in future clinical practice. Biological therapies are playing an increasing role in the management of colorectal cancer. Farnesyl transferase inhibition, inhibition of the epidermal growth factor receptor (EGFR) and the vascular endothelial growth factor (VEGF) are undergoing evaluation in advanced disease. In the adjuvant setting, both passive and active immunotherapeutic approaches have been studied. In addition, a large trial will evaluate the role of cyclo-oxygenase(COX)-2 inhibitors as adjuvant therapy. Further research is required in order to define the optimal sequence and combination of these different cytotoxic and biological therapies, in order to secure the best possible outcome for various subgroups of patients with both early and advanced stage colorectal cancer.